Location on the Human Genetic Linkage Map of 26 Genes Involved in Blood Coagulation - Koeleman, Bobby P C; Reitsma, Pieter H; Bakker, Egbert; Bertina, Rogier M (Thrombosis and Haemostasis, 1997)
Several human genetic linkage maps have been constructed as part of the Human Genome Project. These maps show the positional order of closely linked, highly informative AC-repeat polymorphisms on each human chromosome, and are extremely useful in genetic linkage analysis of inheritable diseases. For a candidate gene approach the current linkage maps are less useful, since they consist mainly of anonymous markers rather than of specific genes. This situation also applies for inheritable disorders of blood coagulation. Numerous genes are involved in the blood coagulation cascade and its regulation, and can be considered as candidate genes for unexplained haemophilia and thrombophilia. We have selected 29 candidate genes that seem to be the ones most likely to be involved in thrombophilia. For 19 genes genotype data were already present in the CEPH database (version 7.0). We typed 7 additional genes in the CEPH reference families, i.e. the factor V, factor XII, protein C, protein S, prothrombin, thrombomodulin, and heparin cofactor II gene. The genotype data were used to integrate these 26 genes in the current genetic linkage map, and to identify closely linked AC-repeat polymorphisms. This information will benefit the investigation of inheritable disorders of blood coagulation, especially thrombophilia.